Association between the body roundness index and osteoarthritis: evidence from NHANES - Ke, Tiancheng; Lai, Jianqiang; Li, Xianmin; Liu, Fuqian; Liu, Wei; Zhong, Chengfan (Frontiers in Medicine, 2024)
Background The body roundness index (BRI) is a quantitative measure used to evaluate the presence of obesity and the distribution of body fat. However, the relationship between the BRI and osteoarthritis (OA) is still unclear. This study aimed to examine the relationship between the BRI and the occurrence of OA. Methods This study was a cross-sectional analysis used to analyze data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. A variety of variables were included in this investigation, which employed logistic regression analysis to assess the correlation between the BRI and OA. The robustness of the results and the impact of stratification variables were evaluated using subgroup and sensitivity analyses. To evaluate the ability of the BRI to predict OA, receiver operating characteristic (ROC) analysis was performed. Results The analysis included 19,717 participants. Participants with OA had a significantly greater BRI than those without OA. Logistic regression analysis revealed a statistically significant positive correlation between the BRI and OA (OR = 1.18, 95% CI = 1.15–1.21, p-value <0.001). Despite the complete adjustment for covariates, this association remained stable (OR = 1.10, 95% CI = 1.04–1.17, p-value = 0.002). The results were corroborated by subgroup and sensitivity analyses, which demonstrated their robustness. Moreover, the BRI exhibited greater predictive accuracy for OA than did BMI. Conclusion The BRI and OA are significantly associated in adults in the United States. The risk of developing OA may be increased by elevated levels of the BRI. Monitoring levels of the BRI is essential to prevent or reduce the prevalence and advancement of OA.